Moisture Resistance, Thermal Stability and Fire Behavior of Unsaturated Polyester Resin Modified with L-histidinium Dihydrogen Phosphate-Phosphoric Acid - Sałasińska, Kamila (Molecules, 2021)
In this paper, the fire behavior of unsaturated polyester resin (UP) modified with L-histidinium dihydrogen phosphate-phosphoric acid (LHP), being a novel intumescent fire retardant (IFR), was investigated. Thermal and thermomechanical properties of the UP with different amounts of LHP (from 10 to 30 wt. %) were determined by thermogravimetric analysis (TG) as well as dynamic mechanical thermal analysis (DMTA). Reaction to small flames was studied by horizontal burning (HB) test, while fire behavior and smoke emission were investigated with the cone calorimeter (CC) and smoke density chamber. Further, the analysis of volatile products was conducted (TGA/FT-IR). It was observed that the addition of LHP resulted in the formation of carbonaceous char inhibiting the thermal decomposition, burning rate and smoke emission. The most promising results were obtained for the UP containing 30 wt. % of LHP, for which the highest reduction in maximum values of heat release rate (200 kW/m(2)) and total smoke release (3535 m(2)/m(2)) compared to unmodified polymer (792 kW/m(2) and 6895 m(2)/m(2)) were recorded. However, some important disadvantage with respect to water resistance was observed.